"Będziecie moimi świadkami po krańce ziemi" (Dz 1,8). Łukaszowa wizja świadectwa z perspektywy Dziejów Apostolskich - Mielcarek, Krzysztof (Verbum Vitae, 2015)
Because of the richness of Lukan theology regarding witness, the author was unable to cover all of its aspects. Thus the study touches only upon its major threads. Besides the obvious issues of the apostles role as witnesses, the content of their witnessing, and its recipients – the study presents some other personalities involved in transmitting the Good News of God’s salvation to humanity. Indeed, the greatest stress is placed on the testimony of God himself. Despite being a constant Mystery for humankind, He never ceases being involved in their history and witnessing to his salvific plans. Although there are only a few texts within Acts that connect the persons of the Trinity to witnessing, one should consider them as fundamental to a full Lukan theology of witness.